Reduced reporting of neuropsychiatric adverse events with tumor necrosis factor alpha inhibitors for hidradenitis suppurativa: caution before concluding for risk reduction. (6th May 2020) - Raschi, E.; Salvo, F.; La Placa, M.; Poluzzi, E.; De Ponti, F.
Abstract : Linked article: M.A. Gupta et al. J Eur Acad Dermatol Venereol 2020;34: e431–e432. https://doi.org/10.1111/jdv.16378 .